Cultural aspects related to pregnancy in the family context: integrative review (Research, Society and Development, 2020)
Objective: to identify in scientific productions the cultural aspects related to pregnancy in the family context. Method: integrative literature review, developed in LILACS databases, with the descriptors “pregnancy” and “culture” and in PubMed, with meshterms “pregnancy”, “culture” and “family relations”. Based on the research question and exclusion criteria, 26 studies were selected. Results: a set of meanings, perceptions, practices and experiences related to the meaning of pregnancy, food and restrictions diverse to pregnant women, sexuality, sex of the baby, choice by way of delivery and the role of the health professional were identified. Conclusion: new ways of thinking and acting in health in the context of care for women and families are needed during the gestational process, considering other dimensions of care in prenatal care and valuing the cultural aspects that are usually little worked by health professionals.